Axillary vein thrombosis in adolescent onset systemic sclerosis. Issue 7 (July 1990) - Leak, A; Patel, K J; Tuddenham, E G; Pearson, J D; Woo, P
Abstract : A 16 year old girl with a two year history of systemic sclerosis developed left axillary vein thrombosis. Prolonged euglobulin clot lysis time, anti-endothelial cell antibodies, and raised von Willebrand factor antigen were shown.